Single & multi beam laser grooving process parameter development and die strength characterization for 40nm node low-K/ULK wafer - Shi K.W.; Yow K.Y.; Lo C. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper describes the development work on single and multi beam laser grooving technology for 40nm node low-k/ULK semiconductor device. A Nd:YAG ultraviolet (UV) laser diode operating at a wavelength of 355 nm was used in this study. The effects of single and multi beam laser micromachining parameters, i.e. laser power, laser frequency, feed speed, and defocus amount were investigated. The laser processed die samples were thoroughly inspected and characterized. This includes the die edge and die sidewall grooving quality, the grooving shape/profile and the laser grooving depth analysis. Die strength is important and critical. Die damage from thermal and ablation caused by the laser around the die peripheral weakens the mechanical strength within the die, causing a reduction in die strength. The strength of a laser grooved die was improved by optimizing the laser process parameter. High power optical microscopy, Scanning Electron Microscopy (SEM), and focused ion beam (FIB) were the inspection tools/methods used in this study. Package reliability and stressing were carried out to confirm the robustness of the multi beam laser grooving process parameter and condition in a mass production environment. The dicing defects caused by the laser were validated by failure analysis. The advantages and limitations of conventional single beam compared to multi beam laser grooving process were also discussed. It was concluded that, multi beam laser grooving is possibly one of the best solutions to consider for dicing quality and throughput improvements for low-k/ULK wafer dicing. The multi beam laser process is a feasible, efficient, and cost effective process compared to the conventional single beam laser ablation process. © 2014 IEEE.